Ultrastructural localization of insulin receptors on adipocytes. - Jarett, L (1975)
The method for preparing a stable, biologically active, covalently linked ferritin--insulin complex has been modified to provide a 25-fold increase in yield compared to the original procedure while reducing the molar fatio of ferritin to insulin to 1:1 from 40:1. Ultrastructural studies of isolated adipocytes revealed specific binding of ferritin--insulin to the cell surface in irregular clusters associated with the glycocalyx coating. The number of ferritin--insulin molecules observed was consistent with the number of sulin molecules observed was consistent with the number of receptors calculated from 125I-labeled insulin binding studies. The ferritin--insulin was not observed in the cytoplasm of the cell but was found on the convave side of surface connected vesicles. These surface connected vesicles were part of an alveolar-like system of plasma membrane invaginations which project in various directions in the cytoplasm and by thin sectioning can appear as pinocytotic-like microvesicles. The morphological observations on ferritin--insulin binding were supported by the finding that 125I-labeled insulin binding was almost exclusively localized to highly purified plasma membranes isolated by fractionation of adipocytes after incubation with 125I-labeled insulin. These data supported the theory that insulin did not need to enter a cell to cause biological effects and was consistent with the negative cooperativity concept of insulin binding to cell receptors.